Implementation of Human Rights Principles in School Administration: Perceptions of Principals and Teachers of Arab Schools at Jerusalem Governorate - Mohammad A. Abdeen; Eman Reyad Mustafa (Journal of Educational and Psychological Studies, 2012)
This study was undertaken during the 2009 /2010 academic year to explore the Arab schools principals' and teachers' perceptions of the degree to which human rights principles were implemented in school administration in Jerusalem Governorate. A stratified random sample of (36) principals, and (475) teachers was chosen; and a 54-item questionnaire covering five fields of human right was developed to solicit data. Both the validity and reliability of the questionnaire were examined. Results showed that the application of human rights principles in school administration -as perceived by principals and teachers- was “moderate”. Results also showed that there were no statistical significant differences (α ≤ 0.05) between the means due to gender, educational qualification, years of experience, and supervising body; while significant differences were found between means due to job title and school stage.